2012
DOI: 10.3892/ol.2012.775
|View full text |Cite
|
Sign up to set email alerts
|

miR-96 regulates FOXO1-mediated cell apoptosis in bladder cancer

Abstract: Abstract. Transitional cell carcinoma (TCC) is one of the most common types of malignancies and a leading cause of genitourinary system cancer mortality worldwide. The tumor suppressor gene FOXO1, a member of the forkhead box O (FOXO) subfamily of transcription factors, is downregulated in a number of cancers, including TCC; however, the underlying mechanisms are poorly understood. In the present study, we used microRNA (miRNA) target prediction algorithms to identify a conserved potential miR-96 binding site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 19 publications
2
56
0
1
Order By: Relevance
“…Guttilla et al (37) demonstrated that miR-96 was overexpressed in breast cancer cell lines, and that it downregulated the expression of FOXO1. Guo et al (74) and Haflidadóttir et al (75) suggested that miR-96 regulates FOXO1-mediated cell apoptosis and proliferation in prostate cancer. The association between FOXO1 and autophagy in multiple types of cancer, including bladder transitional cell carcinoma, prostate cancer and endometrial carcinoma, was identified in recent years (42)(43)(44)47,48,66,76).…”
Section: Discussionmentioning
confidence: 99%
“…Guttilla et al (37) demonstrated that miR-96 was overexpressed in breast cancer cell lines, and that it downregulated the expression of FOXO1. Guo et al (74) and Haflidadóttir et al (75) suggested that miR-96 regulates FOXO1-mediated cell apoptosis and proliferation in prostate cancer. The association between FOXO1 and autophagy in multiple types of cancer, including bladder transitional cell carcinoma, prostate cancer and endometrial carcinoma, was identified in recent years (42)(43)(44)47,48,66,76).…”
Section: Discussionmentioning
confidence: 99%
“…miR-17 is the only validated miRNA whose expression has been shown to be directly regulated by IRE1-mediated cleavage ( 40 ), and has been shown to be involved in tumor aggressiveness in gliobastoma ( 145 ), hepatocellular carcinoma ( 146 ), and prostate ( 147 ), kidney ( 148 ), gastric ( 149 ), and colon ( 150 ) cancers. However, IRE1 has also been implicated in the degradation of other premiRNAs that are involved in cancer development, such as miR-96 , whose overexpression has been observed in bladder ( 151 ), prostate ( 152 ), and breast ( 153 ) cancers and has been shown to possess tumor-suppressor functions in pancreatic cancer ( 154 ). Overall, because RIDD targets are thought to depend on the cellular context (abundance of the respective substrates in a given cell type), the stimuli engaging IRE1 (nature of the UPRosome formed as well as size of the oligomers), and the presence of somatic mutations altering IRE1 conformation, we predict that this specifi c output of the UPR, together with the expression of classic ER stress transcription factors, will drive distinct gene-expression patterns that affect multiple aspects of cancer biology, including control of (i) the tumor cell death/survival balance, (ii) tumor cell invasion and metastasis properties, and (iii) the nature of the tumor stroma.…”
Section: Er Stress-dependent Rna Stability In Cancermentioning
confidence: 99%
“…A literature examination of many of these differentially regulated miRNAs shed some light on their known roles, and many were found to contribute to the formation and/or function of the nervous system (Table 1). Many of these miRNAs also exhibited overlapping cellular functions, contributing to processes such as tumorigenesis [23][24][25][26][27][28][29][30], differentiation [31][32][33], proliferation [34][35][36][37][38], apoptosis [39][40][41][42], and cell cycle regulation [34,43,44]. A subset of the miRNAs was associated with nervous system-specific processes, such as differentiation [45][46][47][48][49], lifespan [50], neurite guidance [51][52][53], or synaptogenesis [54][55][56].…”
Section: Identification Of Mirnas That Were Differentially Regulated mentioning
confidence: 99%